MicroRNA-27a controls the intracellular survival of Mycobacterium tuberculosis by regulating calcium-associated autophagy. Issue 1 (December 2018) - Liu, Feng; Chen, Jianxia; Wang, Peng; Li, Haohao; Zhou, Yilong; Liu, Haipeng; Liu, Zhonghua; Zheng, Ruijuan; Wang, Lin; Yang, Hua; Cui, Zhenling; Wang, Fei; et al.
Abstract Tuberculosis (TB) caused byMycobacterium tuberculosis (Mtb ) kills millions every year, and there is urgent need to develop novel anti-TB agents due to the fast-growing of drug-resistant TB. Although autophagy regulates the intracellular survival ofMtb, the role of calcium (Ca2+ ) signaling in modulating autophagy duringMtb infection remains largely unknown. Here, we show that microRNA miR-27a is abundantly expressed in active TB patients, Mtb -infected mice and macrophages. The target of miR-27a is the ER-located Ca2+ transporter CACNA2D3. Targeting of this transporter leads to the downregulation of Ca2+ signaling, thus inhibiting autophagosome formation and promoting the intracellular survival ofMtb . Mice lacking of miR-27a and mice treated with an antagomir to miR-27a are more resistant toMtb infection. Our findings reveal a strategy forMtb to increase intracellular survival by manipulating the Ca2+ -associated autophagy, and may also support the development of host-directed anti-TB therapeutic approaches. HowMycobacterium tuberculosis (Mtb ) escapes autophagy-mediated clearance is poorly understood. Here, Liu et al. show that Mtb-induced MicroRNA-27a targets the ER-associated calcium transporter CACNA2D3, leading to suppression of antimicrobial autophagy and to enhanced intracellular survival ofMtb .